Othello by Shakespeare traditions and specificity - Nikita S. Futljaev, Dmitry N. Zhatkin, (Opción, 2019)
The article analyzes the features of Aksenov’s translation of the tragedy of Shakespeare (1899) «Othello». In the process of studying genetic, socio-cultural, comparative-historical and historical-typological approaches were used. The Aksenov’s translation of the tragedy of Shakespeare (1899) «Othello», preserved in the Russian State Archive of Literature and Art, as well as its stage version, owned by Zhatkin et al. (1935). Despite the imperfection of the translation of Aksenov and the stage version prepared by Anisimov, one cannot but recognize its main advantage, which consists in responding to mass audience and readers requests of the 1930s.